GBDTL2E: Predicting lncRNA-EF Associations Using Diffusion and HeteSim Features Based on a Heterogeneous Network - Wang, Jiaqi; Kuang, Zhufang; Ma, Zhihao; Han, Genwei (Frontiers in Genetics, 2020)
Interactions between genetic factors and environmental factors (EFs) play an important role in many diseases. Many diseases result from the interaction of genetic and EFs. The long non-coding RNA (lncRNA) is an important non-coding RNA that regulates life processes. To predict the associations between lncRNAs and EFs have important practical significance. However, the recent methods for predicting lncRNA-EF associations rarely use the topological information of heterogenous biological networks or simply treat all objects as the same type, without considering different subtle semantic meanings of different paths in the heterogeneous network. In order to address this issue, a method based on Gradient Boosting Decision Tree (GBDT) to predict the association between lncRNAs and EFs (GBDTL2E) is proposed in this paper. The innovation of GBDTL2E is that which integrates the structural information and heterogenous networks, combines the Hetesim features and the diffusion features based on multi-feature fusion, and uses the machine learning algorithm GBDT to predict the association between lncRNAs and EFs based on heterogeneous networks. The experimental results demonstrate that the proposed algorithm achieves high performance.